Simulation of Turbulent Natural Convection in a Local Zone of Largescale Area Under Conditions of the Radiant Energy Supply; MATEC Web of Conferences; Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) - Nee A. E. Aleksandr Eduardovich (2016, 2016)
Title screen